1999
DOI: 10.1037/0021-9010.84.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Mentor functions and outcomes: A comparison of men and women in formal and informal mentoring relationships.

Abstract: The authors examined the effects of the type of mentoring relationship and the gender composition of the relationship on mentoring functions and career outcomes reported by 352 female and 257 male protégés. Protégés of informal mentors viewed their mentors as more effective and received greater compensation than protégés of formal mentors. Protégés with informal mentors also received more career outcomes than nonmentored individuals, but no significant differences were found between nonmentored and formally me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
684
4
25

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 992 publications
(782 citation statements)
references
References 51 publications
30
684
4
25
Order By: Relevance
“…They show conflicting results for approaches to the pairing process. Some studies of mentor pairs formed by a program coordinator achieved satisfactory relationships (D'Abate and Eddy 2008;Boice 1992a;Ragins et al 2000), while other studies demonstrated that participant input into the pairing process was preferable (Viator 1999;Ragins and Cotton 1999;Allen et al 2006). In a program where the coordinator matched mentors and mentees based on informal knowledge and biographical data about participants, mentors were extremely satisfied with the pairing process (D'Abate and Eddy 2008).…”
Section: Pairing In Mentoring Programs: Previous Studiesmentioning
confidence: 99%
“…They show conflicting results for approaches to the pairing process. Some studies of mentor pairs formed by a program coordinator achieved satisfactory relationships (D'Abate and Eddy 2008;Boice 1992a;Ragins et al 2000), while other studies demonstrated that participant input into the pairing process was preferable (Viator 1999;Ragins and Cotton 1999;Allen et al 2006). In a program where the coordinator matched mentors and mentees based on informal knowledge and biographical data about participants, mentors were extremely satisfied with the pairing process (D'Abate and Eddy 2008).…”
Section: Pairing In Mentoring Programs: Previous Studiesmentioning
confidence: 99%
“…This is in line with the mentoring literature that states that informal mentoring is more beneficial to career development than formal (Chao, et al, 1992;Ragins & Cotton, 1999). However, it is additionally important to acknowledge that although all participants may have had informal mentoring relationships, their pathways were unique due to each one's personal circumstances and goals.…”
Section: Mentor's Summarysupporting
confidence: 81%
“…The fact that Oscar chose, and was able to pursue self-mentoring processes autonomously might therefore be indicative of the impact of his previous mentoring relationship on enhancing his selfdirectedness. As previously mentioned, his mentoring was informal and, in this sense, it has been suggested that informal mentoring functions seem to generate more career outcomes than formal mentoring (Chao, et al, 1992;Ragins & Cotton, 1999).…”
Section: The Need For Pedagogical Knowledge and Self-mentoringmentioning
confidence: 83%
“…Mentoring: Ir ou não Ir, Eis a Questão O desafio dos programas formais é buscar "mimetizar" processos interpessoais naturais por meio de oportunidades frequentes de encontro, treinamento, manejo de expectativas, treinamento e, por vezes, pareamento voluntário 25 .…”
Section: Patrícia Lacerda Bellodi Et Alunclassified